Cow's milk protein allergy or lactose intolerance? Principles of differential diagnosis and diet therapy - S.L. Nyankovskyy; О.S. Nyankovska; H.M. Trotskyy; N.V. Kamut (Zaslavsky O.Yu., 2019)
Clinical gastrointestinal manifestations of cow's milk protein allergy and lactase deficiency such as diarrhea, bloating, colic, and regurgitation are quite similar, which often lead to errors in diagnoses and methods of nutritional correction. Diagnoses such as milk allergy, milk intolerance, as well as lactose intolerance are often used without a clear understanding of the various underlying mechanisms and the consequences that may result from improper diet therapy. The article deals with the differences between cow's milk protein allergy and lactose intolerance. The article presents the algorithm of differential diagnosis of cow's milk protein allergy and lactase deficiency in a child, which enables to correctly determine the diagnosis and prescribe necessary treatment in a timely manner. Timely and correct food intervention significantly reduces the risk of complications and further development of diseases, has a positive economic effect and helps to improve the quality of life of children and their families.